The Students’ Perception toward English Camp of Cokroaminoto Palopo University - Ardhy Supraba; Juwita Crestiani M; Muhammad Hasby; Edi Wahyono; Sunardin Sunardin (DEIKTIS: Jurnal Pendidikan Bahasa dan Sastra, 2025)
This research aims to find out the students’ perception toward English camp of Cokroaminoto Palopo University. The research design of this research was descriptive research. The result of this research shows that the implementation of English camp of Cokroaminoto Palopo University gained very positive perceptions from the students. Most of them agreed that the English camp of Cokroaminoto Palopo University could improve their speaking skill.